Online Learning as e-Learning: The Quality and Results (Critical Analysis) - A. V. Dozhdikov (Высшее образование в России)
This article critically examines the result obtained by researchers at the Higher School of Economics in relation to the results of the experiment to assess the quality of online learning. It is noted that the thesis about the possibility of “complete replacement of traditional forms of education with online education without loss of quality” is distorted in the media, and the conclusions are based on insufficient data. To clarify the conditions of the transition and implementation of online technologies, it is proposed to hold a large-scale experiment with a randomly selection mechanisms for participants of training courses, instructors, disciplines (modules). The article focuses on the fact that while the impact of online education on the psychology and physiology of students has not been sufficiently studied, there is a risk of deteriorating health, as well as a drop in the quality of education. It is proposed to develop temporary standards limiting the maximum time of work online for different categories of students and teachers.The risks of «financial bubbles» in the online education market due to the rush demand after the COVID-19 pandemic for government agencies and private businesses has been identified. The conclusion is made about the priority development of short-term online courses related to the development of rather narrow and applied competencies in demand by the modern information society, about the possible success of online technologies in case of obtaining a “second higher” education and improving qualifications. High-quality online systems in the field of higher education require serious investments in research and development in the field of psychology and pedagogy of education, the use of medical control tools. In the medium term, the benefits of this research, conducted by medical scientists, educators and psychologists, will be used by organizations on the “second wave” of interest to online learning. From an organizational point of view, the correct “rotation” of the contingent of students, when part of the time they study full-time, and part of the time they learn online with computers / tablets and high-quality Internet access, will not lead to a deterioration in the quality of education, but will significantly reduce the spread of the pandemic.